3D Mixing Dynamics in T‐Jet Mixers. Issue 1 (20th November 2018) - Sultan, M. Ashar; Pardilhó, Sara L.; Brito, Margarida S. C. A.; Fonte, Cláudio P.; Dias, Madalena M.; Lopes, José C. B.; Santos, Ricardo J.
Abstract: The dynamic flow field in T‐jet mixers is characterized by means of 3D computational fluid dynamics simulations. The main goal of this work is to identify and discuss the chaotic flow regime in T‐jet reactors and the parameters that enable this flow regime, namely, the critical Reynolds number and design parameters of these mixers. The 3D chaotic flow regime that occurs in T‐jet mixers is described herein with unprecedented detail regarding the mixing scales, flow dynamics, and coherent structures. The mixing scales are proven to be set by the mixer dimensions. The chaotic flow regime in T‐jets is of practical interest due to its capability to promote very fast mixing, although descriptions in the literature are scarce. Abstract : Fully resolved flow dynamics in T‐jet mixers are obtained from 3D computational fluid dynamics simulations, particularly those on chaotic flow regimes that are characterized by a vortex issuing from the jet impingement point. The design and operational conditions to promote the chaotic flow regime are analyzed, and mixing scales and dynamics are assessed.